2022
DOI: 10.3389/fvets.2022.845746
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Monitoring Reveals Persistence of Colistin-Resistant Escherichia coli on a Pig Farm Following Cessation of Colistin Use

Abstract: Colistin-resistant bacteria harboring plasmid-mediated mcr genes are of concern as they may be a cause of serious nosocomial infections. It is hypothesized that cessation of colistin use as a feed additive for pigs will reduce the occurrence and distribution of mcr genes in farms. The aim of this study was to investigate this hypothesis by longitudinal monitoring and characterizing of mcr positive Escherichia coli (MCRPE) isolates after colistin was withdrawn on a central Thailand pig farm that previously had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…Our results confirmed that mcr -positive isolates were resistant to other antibiotics [ 10 , 25 , 26 ]. Except for one isolate, all mcr -positive strains were MDR and 56.1% of them were resistant to ciprofloxacin.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results confirmed that mcr -positive isolates were resistant to other antibiotics [ 10 , 25 , 26 ]. Except for one isolate, all mcr -positive strains were MDR and 56.1% of them were resistant to ciprofloxacin.…”
Section: Discussionsupporting
confidence: 85%
“…The occurrence and distribution of mcr genes was monitored after the withdrawal of colistin at pig and chicken farms. Studies showed different results, and the association between colistin withdrawal and control of the spread of mcr genes was not evidenced [ 25 , 31 , 32 , 33 ]. It should be stressed, however, that in the absence of colistin use, treatment with other antibiotics might co-select mcr genes and favor their spread.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the wide diffusion of tet genes observed in this study is consequent to previous recurrent treatments that have established long-term selective resistant bacteria harboring these genetic elements in the farm environments [ 21 ]. Moreover, other environmental sources of resistance pollution by genetic determinants (water, food, or wild birds) cannot be ruled out [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The six MCRPE strains submitted for whole genome sequencing had colistin MIC values of 4–8 mg/L and had different PFGE profiles and ST types 8 . These MCRPE strains transferred mcr -1 and mcr -3 genes to recipient E. coli J53 at conjugative transfer frequency rate of 1.7–2 × 10 −4 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite numerous cases of colistin resistant Enterobacteriaceae being reported from livestock and humans in Thailand, detailed genomic characterization of mcr -positive E. coli , particularly amongst livestock isolates, is still limited. In this study, six mcr- positive E. coli strains with multi-drug resistance traits 8 were subjected to whole genome sequencing (WGS) and characterization of the plasmids for better understanding of mcr genes dissemination between pigs and the farm environment.…”
Section: Introductionmentioning
confidence: 99%